2016
DOI: 10.1371/journal.pone.0162104
|View full text |Cite
|
Sign up to set email alerts
|

Hell and High Water: Diminished Septic System Performance in Coastal Regions Due to Climate Change

Abstract: Climate change may affect the ability of soil-based onsite wastewater treatment systems (OWTS) to treat wastewater in coastal regions of the Northeastern United States. Higher temperatures and water tables can affect treatment by reducing the volume of unsaturated soil and oxygen available for treatment, which may result in greater transport of pathogens, nutrients, and biochemical oxygen demand (BOD5) to groundwater, jeopardizing public and aquatic ecosystem health. The soil treatment area (STA) of an OWTS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…However, results of this study remain relevant to such areas, specifically in cases where vertical unsaturated space required for treatment is completely lacking. Resulting contamination of floodwaters by sewage effluent has been cited as a growing concern due to the increased transport of pathogens known to impact public health and coastal ecosystems 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, results of this study remain relevant to such areas, specifically in cases where vertical unsaturated space required for treatment is completely lacking. Resulting contamination of floodwaters by sewage effluent has been cited as a growing concern due to the increased transport of pathogens known to impact public health and coastal ecosystems 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Many other states along the eastern United States Coast including Maryland, Georgia, Virginia, and Florida require 60 cm or more separation . Climate change and sea level rise are expected to cause increases in groundwater levels in coastal areas and these increases may influence pollutant treatment by OSW . To plan for these expected changes, it is suggested that new OSW be installed to maximize the vadose zone thickness beneath drainfield trenches.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Climate change and sea level rise are expected to cause increases in groundwater levels in coastal areas and these increases may influence pollutant treatment by OSW. [42] To plan for these expected changes, it is suggested that new OSW be installed to maximize the vadose zone thickness beneath drainfield trenches. This may require increasing the minimum separation distance requirements for OSW, and bringing in fill material to allow the drainfield trenches to be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Post septic tank treatment will be affected by physical, chemical and biological processes that impact on pathogen removal. Temperature, light intensity or UV, pH, soil types, infiltration surfaces, and salinity may affect pathogen concentrations depending on the post-treatment methods applied (Stevik et al, 2004;Chabaud et al 2006;Cooper et al, 2016). The persistence of different microbial species and strains varies in relation to these factors.…”
Section: Physicochemical/biological Factorsmentioning
confidence: 99%
“…Temperature in a septic tank is impacted by the composition of the influent (inputs of blackwater versus heated or cooled greywater). Elevated temperature is expected to increase the death of some pathogens (NOAA, 2011;Cooper et al, 2016;Heger, 2017). Activities of other organisms are reduced in low temperatures leading to reduced predation (Bell et al, 2009).…”
Section: Temperaturementioning
confidence: 99%